Effect of dietary Malic acid on growth performance and body composition of juvenile Siberian sturgeon (Acipenser baerii Brandt, 1869) - Alizade, H.; Ouraji, H.; Falahatkar, B.; Efatpanah, I. (2018)
In this study, the effect of different levels of Malic acid (0.0, 2.5, 5, 7.5 and 10 g/kg diet) was evaluated on growth performance and body composition of juvenile Siberian sturgeon (Acipenser baerii). A total number of 375 fish (33.72±0.60 g initial weight; mean±S.E.) were randomly assigned to 15 circular concrete tanks (1.85 m diameter and 0.25 m depth). The fish were distributed in 5 treatments with 3 replicates and were fed during 8 weeks. The results of growth indices showed that different levels of Malic acid did not have a significant effect on growth performance and food efficiency. food consumption and lipid productive value had a significant difference among the groups (p<0.05). The lowest amount of fat and ash contents was observed in fish fed with 7.5 g/kg Malic acid. Based on the results, the use of Malic acid in this study on juvenile Siberian sturgeon did not have an effect on growth performance, but affected on the body composition. Published